Ankle Inversion Proprioception Impairment in Persons with Chronic Ankle Instability Is Task-Specific. Issue 6 (December 2022) - Han, Jia; Yang, Zonghan; Witchalls, Jeremy; Ganderton, Charlotte; Adams, Roger; Waddington, Gordon
While investigators have often compared ankle proprioception between groups with and without chronic ankle instability (CAI), findings have been inconsistent. Possibly this is because ankle proprioceptive impairment in this population is task-specific. Thus, we aimed to compare ankle inversion proprioception in individuals with and without CAI in two task conditions: (i) when standing (not challenging) and (ii) when on a step-down landing (minimally-challenging). Ankle inversion proprioception was measured in both conditions for 38 recreational sport player volunteers with CAI ( n = 19) and without CAI ( n = 19). We used the Active Movement Extent Discrimination Apparatus (AMEDA) for the standing condition and the Ankle Inversion Discrimination Apparatus-Landing (AIDAL) for step-down landing. From analysis of variance (ANOVA) tests, CAI and non-CAI participants performed equally well on the AMEDA when standing; but the CAI group performed significantly worse than the non-CAI group on the AIDAL step-down landing task ( p = 0.03). Within the non-CAI group, the AIDAL proprioceptive scores, as area under the receiver operating characteristics curve (AUC), were significantly higher than their AMEDA AUC scores ( p = 0.03), while there was no significant difference between AIDAL and AMEDA AUC scores in the CAI group. Cumberland Ankle Instability Tool CAIT scores were significantly correlated with AIDAL scores (Spearman's rho = 0.391, p = 0.015), but not with the AMEDA scores; and there was no significant correlation between the AIDAL and AMEDA scores. Thus, an ankle inversion proprioceptive deficit was evident for persons with CAI on the step-down AIDAL, and in a dose-response way, but not evident on the standing AMEDA, suggesting that ankle proprioceptive impairment is task-specific. Selected proprioceptive tests must present some minimal degree of challenge to the ankle joint in a functional task in order to differentiate CAI from non-CAI participants.